Literature Review: Overview of Heavy Metal Contamination of Shrimp in Indonesia - Zida Sinata Milati - (Media Gizi Kesmas, 2022)
Background : Shrimp is a nutritious source of animal protein and has many benefits for the body. Shrimp production in Indonesia is one of the top 10 shrimp producers in the world, this is in line with the increasing consumption of fish, especially shrimp in Indonesian society. Shrimp that live in fresh water and in sea water always forage at the bottom of the water, namely in sediments, where a lot of solid particles in the form of sand and mud and heavy metals are deposited as a result of the deposition process in the waters, so shrimp is a good indicator of heavy metal pollution. Objectives : The Objectives of this literature review is to describe the condition of heavy metal contamination in shrimp of Indonesia, Hence it is necessary to monitor the concentration of heavy metal contamination in shrimps, so that a warning signals can be given to the society in case the concentration levels cross the threshold limits. Methods : The method used in writing this article is a literatur review, which is a research by conducting a study of several national and international articles. The database used came from ‘Google Scholar' using related keywords and obtained 2160 articles, after screening the topic and inclusion criteria that had been set, 13 articles were obtained which were then carried out by a literature review. Discussion : The tests for a content of heavy metals (Hg, Pb, Cu, Cr, As, Mn, and Zn) of shrimp in several regions in Indonesia using the AAS (Atomic Absorption Spectrophotometer) test method and the color test (Rapid Test Kits) resulted in several variations, for the shrimp samples tested for heavy metal contamination of Hg, Cu, Mn, and Zn in all samples were safe from contamination, while the shrimp samples tested for Pb, Cd, and Cr content had positive and negative results (1 : 2 ratio). Conclusions : Variations in heavy metal content (Hg, Pb, Cd, Mn, Cu, As, and Zn) in shrimp samples with different locations, there are positive and negative shrimp samples for certain heavy metals, can be influenced by several factors but the public is advised to continue to be careful, that is always process shrimp before consumption properly and correctly.   Keywords : Contamination, Heavy metal, and Shrimp